Photovoltaic Fuzzy - MPPT Based Smart Battery Charger for Low Power Applications - Pawar, Aarti S.; Chopade, Nilkanth B.; Kolte, Mahesh T.; Mehta, Hrishikesh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The advent of photovoltaic (PV) modules has revolutionized electricity generation, but their nonlinear characteristics impose constraints on achieving maximum energy output. To address this challenge, the utilization of Maximum Power Point Tracking (MPPT) techniques has become crucial to optimize power generation even in unfavorable conditions. Although MPPT-enabled battery chargers for high-power systems are readily available, there is an increasing need to develop chargers specifically designed for low-power applications. These chargers will ensure efficient power supply during emergencies, catering to the demands of various low-power scenarios. This research paper aims to create a self-contained solar PV charge controller that incorporates MPPT capabilities. The MATLAB/Simulink environment is used to simulate the circuitry, and the charge controller utilizes a buck converter setup. The goal is to accurately track and optimize the solar panel’s maximum power output, which is achieved by implementing the Fuzzy MPPT technique. The effectiveness of the Fuzzy MPPT approach is compared to the Perturb and Observe (P&O) and Incremental Conductance (INC) MPPT strategies in a comparative analysis. Additionally, the battery charge controller (BCC) charges lead-acid and lithium-ion batteries in three stages. MPPT bulk charge, constant voltage (CV) absorption charge, and float charge are among the various stagesThe efficiency of the model is assessed based on its capacity to track MPPT, the effectiveness of battery charging, and the charge controller’s overall performance. The results show that the Fuzzy MPPT technique demonstrates quick tracking of the PV panel’s maximum power point, achieving this in less than 0.5 seconds even when subjected to variations in solar irradiation circumstances. It also accomplishes a remarkable maximum power tracking efficiency of 99.7%.